Relationship between caffeine content and flavor with light intensity of several coffee Robusta clones - Novie Pranata Erdiansyah; Yusianto Yusianto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2012)
Coffee is a refreshing beverage product and its price is determined by physical quality and flavor. An excellent coffee flavor is resulted only from qualified coffee beans, produced by well managed plantation. The objective of this experiment was to study the effect of sunlight intensity entering coffee farm on flavor profiles and caffeine content of Robusta coffee. The experiment was conducted at the field experimental Kaliwining Estate of Indonesian Coffee and Cocoa Research Institute (ICCRI) during 2009–2011. Treatments were Robusta coffee clones and sunlight intensity. Experimental design was split plot design with three replications. Robusta clones used were BP 409, BP 534, BP 936 and BP 939, planted in 2002. The sunligt intensity treatments were 100% (without shade tree), 50—60% (Leucaena leucocephala shade), and 20—30% (Hibiscus macrophyllus and Melia azedarach L. shades). Only red coffee cherries were harvested for flavor and caffeine analysis. Coffee cherries were washed, depulped and sundried until moisture content of less than 12%. The green coffee bean samples were roasted at medium level (Agtron Scale at 65#) for cupping test which involved five expert panelists by using ICCRI protocol. Caffeine content was determined by spectrophotometric method. The experiment result indicated that high sunlight intensity resulted in strong aroma of Robusta coffee, while good flavor coffee need medium light intensity. Cafein content had positive correlation with light intensity entering the coffee farm, whereas cafein content had no direct effect on Robusta coffee flavor.Key words: Coffea canephora, clone, sunlight intensity, flavor, caffeine.